Determination of Hugoniot Elastic Limit (HEL) and Equation of State (EOS) of Ceramic Materials in the Pressure Region 20 GPa to 100 GPa. (2017) - Gautam, P.C.; Gupta, Rajneesh; Sharma, A.C.; Singh, Manjit
Abstract: The light weight ceramics materials like silicon carbide, boron carbide and alumina have major application in vehicle armour and tank amours due to their low density and high compressive strength properties. The mechanical response of these ceramic materials has been investigated using explosive driven plate impact method. In present studies, hugoniot elastic limit (HEL) from pressure-time profile using manganin gauge and shock EOS in the pressure region 20 GPa to 100 GPaof boron carbide, silicon carbide and alumina were determined. In manganin gauge trace, the delayed failure observed also during shock loading.